Peningkatan Hasil Belajar melalui Pembelajaran Kooperatif Tipe STAD pada Pembelajaran Dasar Sinyal Video - Santi Utami (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
This study aims at improving the student’s learning outcomes through the cooperative learning strategy with Student Teams Achievement Division (STAD) at SMKN 1 Saptosari. This was classroom action research (CAR) consisting of planning, action, observation, and reflection. The research subjects were the grade X students of Audio Video Engineering A. The data collection technique used the documentation of daily tests to show the improvement. The data was analyzed with descriptive statistics. This study consisted of three cycles. The mean of test results for the first, second and third cycles were 7.06, 5.9 and 7.09 respectively. It showed that the cooperative learning strategy with STAD could improve the students’ achievement to fulfill the Minimum Mastery Criterion (MMC).